Phalangipus somnathensis Sureandiran, Karuppasamy & Suyani, 2024—a junior synonym of Encephaloides armstrongi Wood-Mason in Wood-Mason & Alcock, 1891 (Crustacea, Brachyura, Inachidae) - Ng, Peter K. L.; Patel, Heris; Trivedi, Jigneshkumar (Zootaxa, 2025)
The recently described epialtid majoid crab, Phalangipus somnathensis Sureandiran, Karuppasamy & Suyani, 2024, from off Gujarat in India is here shown to be a junior synonym of the inachid, Encephaloides armstrongi Wood-Mason in Wood-Mason & Alcock, 1891. The holotype male of P. somnathensis does not have a carapace, but the third maxillipeds, thoracic sternum, pleon and first gonopod structure are diagnostic for E. armstrongi. The carapace as described and figured by the authors was actually based on another specimen and was mistakenly associated with the holotype.